BIOFILM FORMATION AND ELECTRON MICROSCOPIC STUDIES IN MULTIDRUG RESISTANT CLINICAL ISOLATES OF SHIGELLA SPS ISOLATED FROM INFANT’S STOOL, NORTH PART OF KARNATAKA, INDIA - PRABHURAJESHWAR C; KELMANI CHANDRAKANTH R (International Journal of Pharma and Bio Sciences, 2016)
Diarrhoea and acute gastroenteritis are among the leading causes of illness and death in infants and children throughout the world, more than ever in developing countries and also a commending pathogen forming biofilms on many surfaces and latterly, increased resistance scarcity was recommended to be acquired in biofilm environ. The intent of study, to determine the biofilm formation of clinical Shigella isolates and their morphological alters. The present study work involved: 32 multi drug resistance Shigella isolates. Directive of Shigella isolates to form biofilms were screened by test tube and micro titre plate method. Biofilm formation prospective was resolute by growing the tested strains containing tryptic soya broth (TSB) medium with glucose and antibiotic supplement at different incubation periods. Morphological outcome of antibiotic stress isolates were also studied through electron microscopy. The propensity of all articulated Shigella isolates to form biofilms was professed. Base on biofilm-positive phenotype, the strains were classified as high, moderate and weak biofilm formation was distinguished. In two in-vitro screenings: Micro titre plate method is profoundly sensitive method for detection biofilm producing Shigella isolates as compare to test tube method. As drug resistance is a vital mess in Shigellosis, it is foremost to intercept the colonization of the organism by recommending peculiar practices to obviate biofilm formation. Electron microscopic studies relentless the morphology of cell, variability of thickness in cell wall and show up an adaptive response of the Shigella isolate to the ciprofloxacin antibiotic stress and lead to their drug resistance